Percutaneous mechanical thrombectomy using the Rotarex®S device for the treatment of acute lower limb artery embolism: A retrospective single-center, single-arm study - Li, Wenrui; Xing, Yunchao; Feng, Hai; Chen, Xueming; Zhang, Zhiwen (Frontiers in Surgery, 2023)
Objective: Acute limb embolism (ALE) is a challenging and highly morbid and frequently fatal vascular emergency. Percutaneous mechanical thrombectomy (PMT) devices are an alternative treatment to restore perfusion by removing emboli in the limb arterial system. We evaluated the outcomes of treatment of ALE patients using PMT devices in our center. Methods: A retrospective review of ALE patients treated with Rotarex S (Straub Medical) at a single institution from 2018 to 2022 was performed. The primary outcome was technical success defined as complete recanalization of the occluded segment with satisfactory outflow and good capillary filling of the distal parts of the foot without any major or obstructing residual emboli or thrombi either in the treated segment or in the outflow tract without the need for additional catheter-directed thrombolysis (CDT) or conversion to open surgery. Embolised segments treated, treatment outcomes, and perioperative complications were reviewed. Results: A total of 17 ALE patients (29% male, 71% female; mean age, 73 years) underwent PMT procedures. The femoral arteries and popliteal arteries are the most commonly treated vessels, with both present in 59% of the patients. The technical success rate was 100%, but the majority of cases (82%) had concurrent PTA or stentgrafting, and two patients used urokinase during the operation. There was one thrombotic recurrence that required amputation. There were no 30-day deaths. Complications included extravasation after PMT (two), intraoperative embolization of the outflow tract (one), access site hematoma (one), target artery thrombosis (one) and acute kidney injury (one). There were no severe bleeding complications. Conclusions: The Rotarex S device has a satisfactory success rate, although complementary use of various adjunctive techniques is frequently required. It seems to be a moderately effective tool for the treatment of ALE to avoid CDT or open surgery. The device appears to be safe, with low risks of amputation and mortality rates, but special attention should be given to the potential for extravasation and distal embolism.